2017
DOI: 10.1007/s00268-017-4234-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Albumin–Bilirubin Grade Predicts Recurrences After Radical Gastrectomy in Patients with pT2‐4 Gastric Cancer

Abstract: ALBI grade serves as a simple and promising predictive factor for disease-free and disease-specific survival in patients with pT2-4 GC after radical gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 41 publications
(45 reference statements)
4
46
0
1
Order By: Relevance
“…Thus, a proper preoperative assessment of the nutritional status of gastric cancer patients should be performed. Numerous studies have sought to develop a reliable, valid scoring system that can identify patients with poor nutritional status and some systems have been used successfully to predict complications after gastrectomy [36][37][38].…”
Section: Nutritionmentioning
confidence: 99%
“…Thus, a proper preoperative assessment of the nutritional status of gastric cancer patients should be performed. Numerous studies have sought to develop a reliable, valid scoring system that can identify patients with poor nutritional status and some systems have been used successfully to predict complications after gastrectomy [36][37][38].…”
Section: Nutritionmentioning
confidence: 99%
“…Moreover, several studies have found that ALBI is associated with prognostic factors for disease-free survival and overall survival 13. Kanda et al18 reported that ALBI grade 2 patients were more likely to have shorter disease-specific and disease-free survival after radical gastrectomy, compared with that for ALBI grade 1 patients. Additionally multivariable analysis identified ALBI grade 2 as an independent prognostic factor for disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…Alb and bilirubin concentrations to determine the ALBI score are easily measured using standard laboratory tests in most hospitals. Moreover, the ALBI score can serve as a prognostic factor for certain malignancies [91315]. This study revealed that high ALBI scores are associated with shorter time to failure of postoperative adjuvant S-1 monotherapy and caused shorter DFS.…”
Section: Discussionmentioning
confidence: 93%
“…These parameters can be determined by preoperative routine blood test at any hospital and were potentially correlated to nutritional status and functions of the liver, kidney and bone marrow. The following data were retrospectively retrieved from the medical records: white blood cell count, neutrophil count, total lymphocyte count (TLC), platelet count (Plt), total protein, albumin (Alb), cholinesterase, total bilirubin (T-Bil), aspartate aminotransferase, alanine aminotransferase, indices as candidate predictors: CCr (Cockroft-Gault method), ALBI score [ALBI=log10 T-Bil (µmol/L)×0.66+Alb (g/L)×−0.0852], platelet-lymphocyte ratio (PLR) (PLR=TLC/Plt×100), Onodera's prognostic nutritional index (PNI) (PNI=10×Alb g/dL+0.005×TLC) [1213].…”
Section: Methodsmentioning
confidence: 99%